HUBUNGAN KESEIMBANGAN DAN KECEPATAN AKSELERASI TERHADAP KECEPATAN LARI PESERTA EKSTRAKULIKULER PONDOK PESANTREN MODERN BAHARUDDIN - Alvan faishal Ja’far; Bafirman; Hanif Badri; Liza (Jurnal IKEOR, 2024)
Abstract : Abstract: The problem of this research is the low level of 100 meter running speed for the athletic extracurricular participants at the Baharuddin Modern Islamic Boarding School, South Tapanuli Regency, which is thoght to be caused by the lack of balance and reaction sped for the athletic extracurricular participants at the Baharuddin Modern Islamic Boarding School, South Tapanuli Regency. This type of research is correlational research. This research was conducted in May 2023. The sampling technique used a total sampling technique, so the number of samples in this research was 10 participants. The instruments in this research are 1) Modified bass test, 2) Whole Body Reaction Audiovisual, and speed using a 30 meter sprint. Data analysis techniques use simple correlation analysis and multiple correlation. The results of this research are: 1) There is a significant relationship between balance and 100 meter running speed. Athletic extracurricular participants at Baharuddin Modern Islamic Boarding School, South Tapanuli Regency. 2) There is a significant relationship between reaction speed and 100 meter running speed. Athletic extracurricular participants at Baharuddin Modern Islamic Boarding School, Baharuddin Regency. South Tapanuli 3) There is a significant relationship between balance and reaction speed which together contribute to the 100 meter running speed Participants in extracurricular athletics at the Baharuddin Modern Islamic Boarding School, South Tapanuli Regency